Sex-based differences in cell migration on aligned topographies - Yang Hu; Yin Mei Chan; Nicola G. Judge; Matthew L. Becker; Rebecca K. Willits (Scientific Reports)
Abstract Sexual dimorphism has been observed in many physiological and pathological responses, yet few studies incorporate both female and male experimental groups for preclinical work. For the development of biomaterial devices, in vitro studies are essential for design and optimization, and quantitative comparison of female and male cell migratory behavior is a crucial design consideration. In this work, we thoroughly examined sex-based migration on flat controls and aligned nanofiber scaffolds of various diameters using anomalous and random walk models. Male and female cells exhibited significantly different migration on flat substrates, with female cells having increased speed while male cells had higher persistence. Persistence increased with the introduction of aligned fiber topography for female cells, but only affected male cells on the highest fiber diameter. Speed along the axis of alignment differed between sexes on 1.2 and 1.8 µm fibers. Morphological analysis confirmed cell shape was a function of both sex and fiber size. These results provided critical information regarding sex-based cell migration, highlighting the importance of sex within in vitro studies for clinical device design.